2012 IEEE/ASME International Conference on Advanced Intelligent Mechatronics (AIM) 2012
DOI: 10.1109/aim.2012.6265872
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic propulsion of a spiral-type endoscopic microrobot in a real small intestine

Abstract: Abstract-This paper reports on the magnetic propulsion of a spiral-type endoscopic mircorobot in a real small intestine. Magnetic modeling was carried out to design and commission an external electromagnetic system, which wirelessly provides power to the robotic agent. The capsules with different spiral structures were magnetically propelled inside a segment of porcine small intestine. From the results, it is shown that the propulsive velocities of the tested capsules are in the range of 2.5 ~ 35 mm/s when rot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In the industrial and medical fields, most of the magnetic levitating motion requires precise and larger displacement of active motion control. However, there is no dynamic model for the actuating force generated by the rotating magnetic field in current studies, and the control implementation is insufficient [11,12]. Relying on the special structure of the controlled object under the action of an external magnetic field, the object rotates in the liquid to generate a propulsive force, thereby realizing the levitating motion of the controlled object [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In the industrial and medical fields, most of the magnetic levitating motion requires precise and larger displacement of active motion control. However, there is no dynamic model for the actuating force generated by the rotating magnetic field in current studies, and the control implementation is insufficient [11,12]. Relying on the special structure of the controlled object under the action of an external magnetic field, the object rotates in the liquid to generate a propulsive force, thereby realizing the levitating motion of the controlled object [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, 12,13 we have proposed a spiral-type magnetic capsule (shown in Figure 1). We have found that the sliding friction between the capsule and the intestine plays an important role in determining its locomotion capability.…”
Section: Introductionmentioning
confidence: 99%